2012
DOI: 10.1007/s11095-012-0872-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Solid-Form Landscape of Pharmaceutical Hydrates: Transformation Pathways of the Sodium Naproxen Anhydrate-Hydrate System

Abstract: The properties of the polymorphic dihydrate control the transformation pathways of sodium naproxen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 30 publications
5
47
0
Order By: Relevance
“…). Various hydrate forms of sodium naproxen with complex structure (at least monohydrate, dihydrate, and tetrahydrate, as well polymorphic hydrate forms) have been reported in the literature . However, detailed assignment of the molar ratio of water of crystallization for these intermediate species detected was not possible from the Raman spectra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…). Various hydrate forms of sodium naproxen with complex structure (at least monohydrate, dihydrate, and tetrahydrate, as well polymorphic hydrate forms) have been reported in the literature . However, detailed assignment of the molar ratio of water of crystallization for these intermediate species detected was not possible from the Raman spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Various hydrate forms of sodium naproxen with complex structure (at least monohydrate, dihydrate, and tetrahydrate, as well polymorphic hydrate forms) have been re- ported in the literature. [40][41][42][43] However, detailed assignment of the molar ratio of water of crystallization for these intermediate species detected was not possible from the Raman spectra. The estimated fractional amounts of the various solid forms presented in Figure 6b should be interpreted with caution because of the complexity of the multivariate data and the uncertainty in the MCR data analysis.…”
Section: Dissolution Of Sodium Naproxenmentioning
confidence: 99%
“…In this paper we consider the non-steroidal anti-inflammatory drug (NSAID) sodium (S)-naproxen (chemical structure shown in Scheme 1 with applied labelling scheme). The compound is known to exist as an anhydrate (AH), a monohydrate (MH), two dihydrate polymorphs (DH-I and DH-II) and a tetrahydrate (TH) (Di Martino et al, 2001Martino et al, , 2007Malaj et al, 2009;Raijada et al, 2013). A thorough empirical study of the thermodynamic and kinetic aspects of dehydration in the system has been reported by Malaj et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Those authors refer to the various phases as ASN (= AH), MSN (= MH), CSN (= DH-I), DSN (= DH-II) and TSN (= TH). We have also previously studied the transformation pathways for the system using multitemperature dynamic vapour sorption (DVS) and variabletemperature/humidity powder X-ray diffraction (PXRD), and we have identified routes to isolate bulk samples of the various phases (Raijada et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrates, and especially their dehydration properties, are important in the pharmaceutical industry (see, for example, Fujii et al, 2012;Kachrimanis & Griesser, 2012;Raijada et al, 2013). For crystalline hydrates, the dehydration properties are dependent to a large extent on the environment of the water molecules in the crystal structure.…”
Section: Introductionmentioning
confidence: 99%